1992
DOI: 10.1152/ajpheart.1992.263.2.h491
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin modulates K(+)-channel activities of cultured smooth muscle cells from porcine coronary artery

Abstract: The ATP-sensitive K+ channel (KATP channel) and the Ca(2+)-activated K+ channel (KCa channel) were active in cell-attached and excised inside-out patch configurations in cultured smooth muscle cells of the porcine coronary artery. Vasopressin activated the KCa channel (240 pS) when it was applied in the bath in the cell-attached patch mode presumably because of an increase in intracellular Ca2+, but it had no direct effect on the KCa channel. However, vasopressin directly blocked the KATP channel from outside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 0 publications
4
80
0
2
Order By: Relevance
“…Nicorandil has also been shown to activate ATP sensitive K + channels in cultured porcine coronary arterial cells and cells isolated from rat and rabbit portal vein. The unitary conductance is similar to that of the channel activated by nicorandil in cultured porcine coronary arterial cells (30 pS, Miyoshi et al, 1992;Wakatsuki et al, 1992), and of the channel activated by Figure 7 The inhibitory e ect of LY 83583 on nicorandil relaxations. (a) Concentration-response curves for relaxations to nicorandil under control conditions as in Figure 6a, and in the presence of LY 83583 at 10 nM (n=6), 100 nM (n=4), 1 mM (n=6), and 10 mM (n=4).…”
Section: K + Channel Activation By Nicorandilmentioning
confidence: 74%
See 1 more Smart Citation
“…Nicorandil has also been shown to activate ATP sensitive K + channels in cultured porcine coronary arterial cells and cells isolated from rat and rabbit portal vein. The unitary conductance is similar to that of the channel activated by nicorandil in cultured porcine coronary arterial cells (30 pS, Miyoshi et al, 1992;Wakatsuki et al, 1992), and of the channel activated by Figure 7 The inhibitory e ect of LY 83583 on nicorandil relaxations. (a) Concentration-response curves for relaxations to nicorandil under control conditions as in Figure 6a, and in the presence of LY 83583 at 10 nM (n=6), 100 nM (n=4), 1 mM (n=6), and 10 mM (n=4).…”
Section: K + Channel Activation By Nicorandilmentioning
confidence: 74%
“…Clinically, in contrast to other nitrovasodilators, tolerance does not develop on continued application of nicorandil, and this lack of tolerance seems to be due its K + channel opening action (Frampton et al, 1992). K + current activation by nicorandil has been measured directly using patch clamp of smooth muscle cells cultured from porcine coronary artery (Miyoshi et al, 1992;Wakatsuki et al, 1992) and cells isolated from rat and rabbit portal vein (Kajioka et al, 1990;Kamouchi & Kitamura, 1994), but not so far in cells from small arteries. In both portal vein and coronary artery cells, nicorandil has been reported to activate channels that are inhibited by intracellular ATP (K ATP channels); in rat portal vein cells the channel activated by nicorandil has been reported to also be activated by intracellular Ca 2+ (Kajioka et al, 1990), while in rabbit portal vein cells the channel is activated by intracellular nucleoside diphosphates as well as inhibited by ATP (Kamouchi & Kitamura, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Suppression of the outward potassium current might also be expected to decrease the threshold and increase the number of action potentials triggered by EPSPs, an effect seen in several of the neurons tested. Vasopressin closes ATP-sensitive K ~ channels in cultured smooth muscle cells [74] and in insulin secreting cells [41]. This and other effects of VP on brain neurons, such as reversible depolarization, increase in input resistance and spontaneous activity, and activation of a voltage-dependent inward current [38,43,47,51,75], could thus be a result of different intracellular effector pathways being activated by these peptides via the same or different membrane receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The Kc, channel and KAT P channel have been observed mainly in cell-attached and inside-out patch configurations in the cultured smooth muscle ceils of porcine coronary artery [7,14]. Standen et al [15] showed that EDHF opens the KATP channel.…”
Section: Discussionmentioning
confidence: 99%